Polystyrene microplastics impair the functions of cultured mouse Leydig (TM3) and Sertoli (TM4) cells by inducing mitochondrial-endoplasmic reticulum damage - Giulia Grillo; Sara Falvo; Debora Latino; Gabriella Chieffi Baccari; Massimo Venditti; Maria Maddalena Di Fiore; Sergio Minucci; Alessandra Santillo (Ecotoxicology and Environmental Safety, 2024)
Many laboratory studies demonstrated that the exposure to microplastics causes testosterone deficiency and spermatogenic impairment in mammals; however, the mechanism underlying this process remains still unclear. In this study, we investigated the effects of polystyrene microplastics (PS-MP) on the proliferation and functionality of cultured Leydig (TM3) and Sertoli (TM4) cells, focusing on the mitochondrial compartment and its association with the endoplasmic reticulum (ER). The in vitro exposure to PS-MP caused a substantial reduction in cellular viability in TM3 and TM4 cells. In TM3 cells PS-MP inhibited the protein levels of StAR and of steroidogenic enzymes 3β-HSD and 17β-HSD, and in TM4 cells PS-MP inhibited the protein levels of the androgen receptors other than the activity of lactate dehydrogenase (LDH). PS-MP inhibited the functions of TM3 and TM4, as evidenced by the decrease of the phosphorylation of ERK1/2 and Akt in both cell lines. The oxidative stress caused by PS-MP decreased antioxidant defense in TM3 and TM4 cells, promoting autophagic and apoptotic processes. Furthermore, we found mitochondrial dysfunction and activation of ER stress. It is known that mitochondria are closely associated with ER to form the Mitochondrial-Associated Endoplasmic Reticulum Membranes (MAM), the site of calcium ions transfer as well as of lipid biosynthesis-involved enzymes and cholesterol transport from ER to the mitochondria. For the first time, we studied this aspect in PS-MP-treated TM3 and TM4 cells and MAMs dysregulation was observed. This study is the first to elucidate the intracellular mechanism underlying the effects of PS-MPs in somatic testicular cells, corroborating that PS-MP might be one of the causes of an increase in male infertility through the impairment of steroidogenesis in Leydig cells and of the nurse function of Sertoli cells. Thus, our findings contributed with new information to the mechanism underlying the effects of PS-MP on the male reproductive system.